Gastroscopy Following a Positive Fecal Occult Blood Test and Negative Colonoscopy: Systematic Review and Guideline - Johane Allard; Roxanne Cosby; M Elisabeth Del Giudice; E Jan Irvine; David Morgan; Jill Tinmouth (Canadian Journal of Gastroenterology)
BACKGROUND: A sizeable number of individuals who participate in population-based colorectal cancer (CRC) screening programs and have a positive fecal occult blood test (FOBT) do not have an identifiable lesion found at colonoscopy to account for their positive FOBT screen.